PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS POP UP DI KELAS XI IPS SMA N 8 KOTA JAMBI - Tiara Luvita, Satriyo Pamungkas (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract          The problems that occur in SMA N 8 Jambi City in learning history are less interesting and the lack of media that supports the history learning process. The formulation of the problem in this study how to develop pop up media in history lessons in SMA N 8 Jambi City. The purpose of this study was to explain the development of pop up media in history lessons at SMA N 8 Jambi City.          This research is a research and development (R & D) which adopts the steps of media development according to Lee And Owens. The sequence of steps in the process is systematically arranged and each step of development has a clearly arranged sequence of development steps. The research and development procedure in the Lee & Owens model consists of five stages, namely (1) assessment / analysis (assessment / analysis) which includes needs analysis and front-end analysis, (2) design ( design), (3) development, (4) implementation, and (5) evaluation.          The results of the research and development of the Pop Up history learning media in the first stage of the quality of the learning media on average had a good percentage value, in the second stage the presentation was very good, in the third stage the presentation was very good, so the average media presentation was very good. In the assessment of the expert team consisting of media and material experts from the media experts themselves, not much was improved, only needed to add a few items in the media and material, the media was also worth testing. In the trial phase I for presentation, the score was 5.4, it was good, in the trial phase II the value of 6.0 was classified as very good and at the third stage of the 16.2 trial it was very good.          The conclusion of the research and development of Pop Up based learning history media in class XI IPS SMA N 8 Jambi City consists of five steps in accordance with the steps of media development according to Lee And Owens. The media is classified as Very Good based on the achievement of the quality of the media and the achievements of the expert team.Keywords: Research and Development, Pop Up Learning Media AbstrakPermasalahan yang terjadi di SMA N 8 Kota Jambi dalam pembelajaran sejarah kurang menarik dan kurangnya media yang mendukung proses pembelajaran sejarah. Rumusan masalah dalam penelitian ini bagaimana pengembangan media pop up dalam pelajaran sejarah di SMA N 8 Kota Jambi. Tujuan dari penelitian ini untuk menjelaskan pengembangan media pop up dalam pelajaran sejarah di SMA N 8 Kota Jambi.Penelitian ini merupakan penelitian dan pengembangan (R&D) yang mengadopsi langkah-langkah pengembangan media menurut dari Lee And Owens urutan langkah dalam prosesnya tersusun secara sistematis dan setiap langkah pengembangan memiliki urutan langkah pengembangan yang tersusun jelas. Prosedur penelitian dan pengembangan dalam model Lee & Owens terdiri dari lima tahap, yaitu (1) penilaian/analisis (assessment/analysis) yang meliputi analisis kebutuhan (need assessment) dan analisis awal akhir (front-end analysis), (2) desain (design), (3) pengembangan (development), (4) implementasi (implementation), dan (5) evaluasi (evaluation).Hasil penelitian dan pengembangan media pembelajaran sejarah Pop Up pada tahap pertama kualitas media pembelajaran rata-rata presentase nilai terbilang Baik, pada tahap kedua presentasi tebilang Sangat Baik, pada tahap ketiga presentasi terbilang Sangat Baik, sehingga rata-rata presentasi media tergolong Sangat Baik. Pada penilaian tim ahli yang terdiri  dari ahli media dan materi dari ahli media sendiri tidak banyak yang diperbaiki hanya perlu menambah beberpa item di media dan materi, media pun layak untuk diuji cobakan. Pada tahap uji coba I untuk presentasi nilai 5,4 tergolong Baik, pada tahap uji coba II presentasi nilai 6,0 tergolong Sangat Baik dan pada tahap uji coba yang ke III 16,2 tergolong Sangat Baik.Kesimpulan dari penelitian dan pengembangan media pembelajaran sejarah berbasis Pop Up di kelas XI IPS SMA N 8 Kota Jambi terdiri dari lima langkah sesuai dengan langkah-langkah pengembangan media menurut Lee And Owens. Media tergolong Sangat Baik berdasarkan hasil pencapaian pada kualitas media dan pencapaian dari tim ahli.Kata kunci: Penelitian dan Pengembangan, Media Pembelajaran Pop Up